2009
DOI: 10.1007/s10653-009-9274-1
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination of surface soils of industrial city Sialkot, Pakistan: a multivariate and GIS approach

Abstract: In this study concentrations of selected metals viz., Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Na, Ni, Pb and Zn in surface soils of Sialkot city known worldwide for tanneries and pharmaceutical industries were measured to assess the status of urban soil pollution and to identify sources of contamination. Hierarchical cluster analysis (HACA) indicated concentrations of Mg and Ca related to parent rock material, Cd, Co, and Pb with traffic related activities, Cr, Cu, Ni and Zn either associated with automobiles activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 42 publications
(82 reference statements)
4
53
4
Order By: Relevance
“…Elevated Na concentration can damage soil structure in certain soil types by limiting water movement and replacing Ca/Mg ions affecting plant growth. Na levels (1,782 mg/kg) in our earlier study on urban soils of Sialkot were quite lower than present study due to substantial tanneries input (Malik et al 2010). Mg becomes available to plants at higher pH.…”
Section: Resultscontrasting
confidence: 77%
See 3 more Smart Citations
“…Elevated Na concentration can damage soil structure in certain soil types by limiting water movement and replacing Ca/Mg ions affecting plant growth. Na levels (1,782 mg/kg) in our earlier study on urban soils of Sialkot were quite lower than present study due to substantial tanneries input (Malik et al 2010). Mg becomes available to plants at higher pH.…”
Section: Resultscontrasting
confidence: 77%
“…Chromium showed stronger affinities with OM with higher level of enrichment and accumulation and is highly toxic to biological organisms (Kabata-Pendias 2004). Relation of Na and Ca with OM % was also described by Malik et al (2010) in urban soils of Sialkot district with low OM contents which ranged from 0.04-0.7 %. Linear regression analysis revealed that soil properties viz.…”
Section: Heavy Metalsmentioning
confidence: 84%
See 2 more Smart Citations
“…Pb released from emissions gets translocated from the roots to the shoot and leaves in plants (Christiana and Samuel 2013). Urban soils are marked with elevated levels of heavy metals due to extensive anthropogenic activities related to vehicular emissions and traffic, industrial and urban waste, mining, smelting and manufacturing by metal industries, wear and tear of tires, building materials and road activities, fertilizers and agricultural run-off (Lu et al 2010;Mahanta and Bhattacharyya 2011;Malik et al 2010;Montoneri et al 2014). Heavy metal accumulation in soil, their origin and interactions with soil properties act as bioindicators in many environmental-monitoring studies (Qishlaqi and Moore 2007).…”
Section: Introductionmentioning
confidence: 99%